Short-term tundra plant-community nutrient responses to herbivory and warming: New insights from Near infrared-reflectance spectroscopy methodology - Petit Bon, Matteo (UiT The Arctic University of Norway, 2020)
In the long-term, herbivores and climate warming have been shown to alter nutrient levels in tundra plant communities by changing the functional composition of the vegetation. Here, I asked the extent to which they affect tundra plant-community nutrient levels in the short-term by directly modifying the chemistry of plants. I first developed a time- and cost-effective method that allowed me to account for the high variability in nutrient-related plant traits among plant individuals, and further scale up to the plant-community level (Paper I). Then, I applied such methodology to investigate short-term (one/two-year) plant-community nutrient-level responses to herbivores in sub-Arctic/alpine tundra-grasslands (Finnmark) and to herbivory and warming across different habitats in a high-Arctic ecosystem (Svalbard). Herbivory and warming were key, short-term modifiers of tundra plant-community nutrient levels, thus affecting plant-community nutrient dynamics (Paper II), herbivore forage quality (Papers III, V) and the amount of nutrients available to herbivores in summer (Paper V), and the biogeochemistry of the ecosystem (Paper IV). This thesis provides clear evidence that herbivores and climate warming cause immediate changes in tundra plant-community nutrient levels, and that these changes are happening at a much shorter time-scale than previously revealed. Considerable short-term changes in plant-community nutrient levels, as those detected in this work, are likely to have strong implications for the immediate functioning of tundra ecosystems and the trophic interactions established therein.